تفعيل المشاركة الشعبية كأداة أساسية لإعداد مخططات تنظيمية أكثر استدامة دراسة حالة مدينة اللاذقية في سورية - عابدين, محمد يسار; ميَا, رولا; ميَا, صفاء (Latakia University Journal -Engineering Sciences Series, 2014)
تعد المشاركة الشعبية إحدى أهم أدوات التنمية الحضرية المستدامة لإعداد مخططات تنظيمية أكثر ملاءمة، لكنّها تشكّل في الوقت ذاته تحدياً للمعنيين من حيث إيجاد الآلية والنموذج الملائم لتفعيلها وفق خصائص ومتطلبات المدن وحاجات ساكنيها. لذلك انطلق البحث من تأسيس قاعدة نظرية خاصة بعملية المشاركة المجتمعية بهدف التّعرف على مفهومها وأشكالها ودورها في تنمية المدن وتحديد عوائقها في إعداد خطط التنمية الحضرية، ليعتمد بعد ذلك على دراسة تجارب الدول المختلفة عالمياً ومحلياً حول مسألة تفعيل المشاركة كأداة مرجعية لإعداد المخططات التنظيمية لمدنها وتقييمها للاستفادة منها بما يتلاءم مع واقع مدينة اللاذقية، ثم القيام بالدراسة التحليلية لواقع المشاركة في المدينة من خلال الاستعانة بالاستبيان لمعرفة أهمية المشاركة لدى السكان ومدى مشاركتهم في إعداد المخطط التنظيمي للمدينة ,واستجابتهم لها في وضع خطط مدينتهم وتحديد الآلية المفضلة لديهم، ليخلص البحث إلى اقتراح النموذج التشاركي المناسب للظروف المحلية لمدينة اللاذقية لتكون المشاركة الشعبية أكثر فاعلية وتتم وفق آلية عمل تكون على اتصال مباشر مع السكان وتعكس آرائهم وتطلعاتهم. The public participation is one of the most important tools for sustainable urban development to prepare more appropriate master plans, but at the same time it forms a challenge to those concerned in terms of finding an appropriate mechanism and model to be activated according to the characteristics and requirements of the cities and the needs of their residents. The research began from establish the theoretical base of the community participation process to know the concept of it, forms, impediments in the preparation of urban development plans and to depend after that on study the experiences of different countries globally and locally about active the participation as a reference tool for the preparation of master plans for it,s cities, and evaluated them to utilize in line with the reality of Lattakia, then do the analytical study of the reality of participation in the city, through the use of the questionnaire to determine it,s importance to population and and the extent of their participation in the preparation of master plans of the city and acceptability of it to preparation the plans for their city and determine their favorite mechanism, to research concludes to Suggestion the appropriate Participatory model to the local conditions of lattakia city to be public participation more effective with a mechanism of action in direct contact with the population and reflects their views and aspirations...